Faktor Organisasi dengan Kinerja Penyuluh Keluarga Berencana di Kabupaten Jember - Arta, Magdalena Yuni; Hermawati, Ema; Sandra, Christyana; Witcahyo, Eri (Universitas Wiralodra, 2025)
The coverage of active KB participants has a target based on the Estimated Community Demand (PPM), so each year it is expected that the achievements will meet or exceed the target. The problem lies in the significant disparity in the coverage rates of new family planning participants, based on the 2023 data on the achievements of new participants from government and private sectors, the districts with the lowest achievements of new KB participants were Patrang (7.22%), Sukorambi (8.41%), Balung (9.98%), Arjasa (12.87%), Mayang (20.20%), Jelbuk (27.87%), Silo (28.87%), and Umbul Sari District (29.58%). The districts with the highest achievements were Sukowono (719.27%), Wuluhan (694.80%), Tempurejo (644.23%), and Rambipuji (596.35%). The purpose of this study was to analyze organizational factors associated with the performance of KB Counselor. This study employed a quantitative approach with a cross-sectional design. The independent variables were age, years of service, perception of rewards, work motivation, and leadership, while the dependent variable was the performance of KB Counselor. Data analysis included univariate, bivariate, and multivariate analyses using logistic regression. The results showed that there was a significant relationship between work motivation (p-value = 0.045) and leadership (p-value = 0.000) with the performance of KB Counselor, while no significant relationship was found between age (p-value = 0.405), years of service (p-value = 0.513), and perception of rewards (p-value = 1.000) with performance. The most dominant variable associated with KB Counselor performance was leadership, with an OR = 11.2 (95% CI = 2.2–56.2).